Histological Assessment of Pioglitazone Preventive Effect in Glycerol Contrast-Induced Nephropathy in Rats - Mousleh, Rama; Al Laham, Shaza (Journal of Pharmacy and Nutrition Sciences, 2017)
Contrast-induced nephropathy (CIN) remains as a problem of radiographic procedures with high incidence and mortality rates. This study aims to histologically assess the ability of Iohexol to induce nephropathy in rats injected with Glycerol; then investigate the Pioglitazone renoprotective effect on this CIN model in rats. 35 male Albino Wistar rats were randomly divided into 5 groups (n=7/group): healthy (A), Glycerol (B), Glycerol+ Iohexol (C), Glycerol + Iohexol + Pioglitazone (D), Pioglitazone alone (E). Groups (B), (C), and (D) were intramuscularly injected with Glycerol 25% (10 ml/kg). Iohexol (350 mg I/ml, 8,6 ml/kg) was injected through a caudal vein in groups (C) and (D). Pioglitazone (10 mg/kg) was orally administered for 4 days, to groups (D) and (E). Rats were sacrificed on the fifth day. Kidney samples were collected for histological assessment. The results show that the histopathological scores and kidney weight / body weight ratio in group (C), were significantly increased compared with group (B) and (A). These changes were significantly reversed in rats treated with Pioglitazone (group D). In conclusion, Iohexol could cause renal injury in rat kidneys previously damaged by Glycerol. Pioglitazone was able to protect the kidneys from histological alterations.